Routing for applications in NoC using ACO-based algorithms - Silva Junior, Luneque; Nedjah, Nadia; de Macedo Mourelle, Luiza (Applied soft computing, 2013)
[Display omitted] ► A static routing for applications in Network-on-Chips is proposed. ► We used algorithms based on ant colony optimization to reduce congestion delays in packet transmission. ► Simulations were performed by submitting the network to a large number of synthetic applications. ► The analysis of the delay in transmission time of the application shows the ACO-based routing achieving better results than other widely adopted routing algorithms. Networks-on-Chips (NoCs) have been used as an interesting option in design of communication infrastructures for embedded systems, providing a scalable structure and balancing the communication between cores. Because several data packets can be transmitted simultaneously through the network, an efficient routing strategy must be used in order to avoid congestion delays. In this paper, ant colony algorithms were used to find and optimize routes in a mesh-based NoC, where several randomly generated applications have been mapped. The routing optimization is driven by the minimization of total latency in packets transmission between tasks. The simulation results show the effectiveness of the ant colony inspired routing by comparing it with general purpose algorithms for deadlock free routing.